Engineered Magnetic Nanocomposites to Modulate Cellular Function. Issue 9 (6th November 2021) - Filippi, Miriam; Garello, Francesca; Yasa, Oncay; Kasamkattil, Jesil; Scherberich, Arnaud; Katzschmann, Robert K.
Abstract: Magnetic nanoparticles (MNPs) have various applications in biomedicine, including imaging, drug delivery and release, genetic modification, cell guidance, and patterning. By combining MNPs with polymers, magnetic nanocomposites (MNCs) with diverse morphologies (core–shell particles, matrix‐dispersed particles, microspheres, etc.) can be generated. These MNCs retain the ability of MNPs to be controlled remotely using external magnetic fields. While the effects of these biomaterials on the cell biology are still poorly understood, such information can help the biophysical modulation of various cellular functions, including proliferation, adhesion, and differentiation. After recalling the basic properties of MNPs and polymers, and describing their coassembly into nanocomposites, this review focuses on how polymeric MNCs can be used in several ways to affect cell behavior. A special emphasis is given to 3D cell culture models and transplantable grafts, which are used for regenerative medicine, underlining the impact of MNCs in regulating stem cell differentiation and engineering living tissues. Recent advances in the use of MNCs for tissue regeneration are critically discussed, particularly with regard to their prospective involvement in human therapy and in the construction of advanced functional materials such as magnetically operated biomedical robots. Abstract : Nanocomposites combining magnetic nanoparticles and polymers can be produced in various morphologies and retain remote physical controllability through application of external magnetic fields. These materials can be used for biophysical modulation of cell behaviors including proliferation, adhesion, and stem cell differentiation with potential impact on the engineering of living tissues and construction of advanced materials for biohybrid robots.